Dealing with the past for a peaceful future?: analysing the effect of transitional justice instruments on trust in postconflict societies - Fiedler, Charlotte (International journal of transitional justice, 2023)
Can dealing with a history of violent conflict through transitional justice help to rebuild social trust? Addressing three gaps in the current literature, we (1) analyse the effect of transitional justice on social trust, thereby going beyond the predominant focus on renewed violence; (2) use novel, handcoded data to take donor support for transitional justice into account, a relevant but mostly overlooked factor; and (3) systematically investigate the combined effect of transitional justice instruments using qualitative comparative analysis. The analysis covers 24 cases in 19 postconflict countries over the period 1990–2010. Our results indicate that transitional justice needs to go beyond a narrow focus on victims or perpetrators to foster trust in postconflict societies. We find that combining victim restitution with amnesties or taking a broader, societal approach by focusing on truth-finding or bridge-building activities can increase trust. Moreover, international transitional justice support can play an important role in fostering trust, even in the absence of major national transitional justice processes.